Berberine and folic acid co-modified pH-sensitive cascade-targeted PTX-liposomes coated with Tween 80 for treating glioma. (1st September 2022) - Yang, Chunyan; Yang, Zhongzhen; Wang, Siqi; Chen, Jinxia; Liu, Qijun; Tianle Huang,; Hai, Li; Lu, Runxin; Wu, Yong
Graphical abstract: Highlights: For the first time, berberine was modified with cholesterol (BBR-Chol) and achieved excellent mitochondrial targeting effects. For the first time, berberine was used as mitochondrial-targeting ligand for the treatment of glioma. We broke the traditional concept and designed novel pH-responsive cascade-targeted liposomes (Tween 80-BBR + FA-Lips) based on berberine, folic acid and Tween 80. The coating of Tween 80 on the surface of liposomes gives the liposomes the ability to cross the blood–brain barrier. We chose the acylhydrazone bond as the pH-responsive bond which can conceal the positive charge of berberine in normal tissues, when liposomes enter the tumor cells, the acid-sensitive hydrazone bond hydrolyzes gradually to expose berberine. Abstract: Chemotherapy is a conventional treatment for glioma, but its efficacy is greatly limited due to low blood–brain barrier (BBB) permeability and lack of specificity. Herein, intelligent and tumor microenvironment (TME)-responsive folic acid (FA) derivatives and mitochondria-targeting berberine (BBR) derivatives co-modified liposome coated with Tween 80 loading paclitaxel (PTX-Tween 80-BBR + FA-Lip) was constructed. Specifically speaking, liposomes modified by FA can be effectively target ed to glioma cells. BBR, due to its delocalized positive electricity and lipophilicity, can be attracted by mitochondrial membrane potential and concentrate on mitochondria to achieve mitochondrial targeting and induce cell apoptosis. By simultaneously modifying the liposome with FA and BBR to deliver drugs, leads to a good therapeutic effect of glioma through FA-based glioma targeting and BBR-based mitochondrial targeting. In addition, the surface of the liposome was coated with Tween 80 to further improve BBB penetration. All results exhibited that PTX-Tween 80-BBR + FA-Lip can observably improve the chemotherapy therapeutic efficacy through the highly specific tumor targeting and mitochondrial targeting, which can provide new ideas and methods for the targeted therapy of glioma.